2005
DOI: 10.1097/00042737-200505000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease in South Asians resident in Britain: comparison with white Caucasian coeliac patients

Abstract: South Asians with coeliac disease are less likely to present with 'irritable bowel syndrome' symptoms, but more likely to have features of vitamin D deficiency and iron deficiency, and have a higher alkaline phosphatase than white Caucasians. The differences in HLA alleles seen in South Asians with coeliac disease compared with white Caucasian patients suggests that among the South Asians, non-HLA regions may play a stronger role in disease susceptibility and presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…In the United States, a greater proportion of HLA DQ8 and a smaller proportion of DQ2 than in Europe have been reported. 9 HLA DQ2 and DQ8 frequencies similar to those observed in the USA have been described in Asian10, Cuban11 and Chilean12 populations.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the United States, a greater proportion of HLA DQ8 and a smaller proportion of DQ2 than in Europe have been reported. 9 HLA DQ2 and DQ8 frequencies similar to those observed in the USA have been described in Asian10, Cuban11 and Chilean12 populations.…”
Section: Introductionsupporting
confidence: 71%
“…Butterworth et al, in England, demonstrated that patients of Indian origin had lower frequency of HLA DQ2 than those of British origin 10. Lower frequencies of HLA DQ2 and higher frequency of HLA DQ8 than European have also been described among celiac disease patients in the United States (82% DQ2 and 16% DQ8 only) and in Cuba (86% DQ2) 11,17 …”
Section: Discussionmentioning
confidence: 94%
“…CD has been described in South Asian patients who had immigrated to Europe or to North America [29,30,31,32]. A recent Italian multicenter study on immigrant children with CD showed that 3 of the children that migrated to Italy were native to Pakistan and 1 to Sri Lanka [32].…”
Section: Celiac Disease In Asiamentioning
confidence: 99%
“…It would be expected that coeliac disease might develop in these populations and their descendants when they move to other parts of the world where wheat is eaten, and this was observed almost 40 years ago in children of Asian immigrants to Britain11 12 and confirmed in adults in Britain13 14 and Canada 15…”
Section: Introductionmentioning
confidence: 96%